PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF PADA MATA PELAJARAN IPAS DI KELAS V SDN 16 KOTO BARU - M. Anggrayni; Eka Filahanasari; Puji Astuti (STKIP Subang, 2024)
Research is one of the main pillars in a country’s development.to achieve optimal educational goals, good curriculum development is very important. This research is based on the limitations of interesting learning media so that students have not been able to increase their motivation and focus on learning. The aim of this research is to produce interactive video learning media for science and science subjects in fifth grade at SDN 16 Koto Baru. The type of research carried out is research & development (R&D).with the ADDIE model consisting of five stages, namely (1) analyze,(2) design,()development,(4) implementation,(5) evaluation.the validation results of interactive video learning media were assessed by five expert validators, namely, material validation results of 85% were categorized as very valid, design validation results of 80% were categorized as very valid. The results of the teacher response questionnaire data analysis, wich was rated by teachers as getting an average of 88% were categorized as very practical. Based on the results of the effectiveness of the results of the learning assessment of fifth grade students,an average of 91,0% was categorized as very effective.